Synthesis and characterization of biodegradable polyurethanes made from cholic acid and l-lysine diisocyanate ethyl ester. (July 2019) - Acik, Gokhan; Karabulut, Huseyin Riza Ferhat; Altinkok, Cagatay; Karatavuk, Ali Osman
Abstract: In this work, a series of biodegradable polyurethanes (PURs) based on cholic acid (CA) andl -lysine diisocyanate ethyl ester (L-LDI) that are renewable difunctional building blocks is synthesized by step-growth polymerization. Step-growth polymerizations between CA and L-LDI are conducted at different loading ratios by mole ([CA]/[L-LDI] (n/n) = 1:1; 1:2 and 1:4) to investigate the effect on wettability, thermal, and biodegradable properties of final PURs. The intermediates and resulting PURs are characterized by Fourier transform infrared spectroscopy (FT-IR), water contact angle measurements (WCA), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Moreover, biodegradability of obtained PURs is also investigated by conducting enzymatic degradation experiments. The experimental results reveal that PURs having higher L-LDI loading exhibit higher hydrophobic and thermal properties, while lower biodegradable characteristic compared to others. Thus, it is clear that the obtained PURs have great potential for several applications particularly in the fields of drug delivery and tissue engineering requiring biodegradable properties. Graphical abstract: Image 1 Highlights: The syntheses of biodegradable polyurethanes (PURs) are achieved via step-growth polymerization between CA and L-LDI. Results suggest that by increasing L-LDI hydrophobicity and thermal properties are enhanced, but biodegradation is lowered. These fully bio-based PURs might be used as new materials particularly in tissue engineering and biomedical fields.